Development of a Physics Module on Work and Energy Based on STEM Education for Vocational High School Students - Ratika Sekar Ajeng Ananingtyas (Jurnal Pendidikan Sains, 2020)
The need for human resources who have knowledge and skills in the STEM fields is getting bigger. However, from the results of research by PISA, Indonesian students' scores in science, reading, and mathematics were still low. This research was conducted to develop a physics module based on STEM education for vocational high school students and to test it’s feasibility. This research adapted the Dick and Carey development research design. The data were obtained from questionnaires about the feasibility and were analyzed qualitatively and quantitatively. From the results of the validation and feasibility test, the module was very feasible to use.